2005
DOI: 10.1007/s00367-005-0213-6
|View full text |Cite
|
Sign up to set email alerts
|

ROV study of a giant pockmark on the Gabon continental margin

Abstract: A giant, 800-m wide pockmark, called Regab, was discovered along the Equatorial African margin at 3160-m water depth and was explored by remote operated vehicle (ROV) as part of the Zaiango (1998Zaiango ( -2000 and Biozaire (2001Biozaire ( -2003 projects carried out conjointly by TOTAL and a number of French research institutes. A microbathymetric map obtained using the ROV sensors shows that the pockmark actually consists of a cluster of smaller pockmarks aligned N70 along a 15-m deep depression. Methane was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 46 publications
5
94
0
2
Order By: Relevance
“…The first seep community described in the South East Atlantic was discovered in 1998 on a giant pockmark along the Equatorial African margin at 3150 m water depth (Ondréas et al, 2005). Submarine pockmarks are crater-like depressions that are typically wide (10-800 m in diameter), shallow (up to 45 m deep) features, occurring in most seas, oceans and in many diverse geological settings (Hovland et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The first seep community described in the South East Atlantic was discovered in 1998 on a giant pockmark along the Equatorial African margin at 3150 m water depth (Ondréas et al, 2005). Submarine pockmarks are crater-like depressions that are typically wide (10-800 m in diameter), shallow (up to 45 m deep) features, occurring in most seas, oceans and in many diverse geological settings (Hovland et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hovland & Judd (1988) found that North Sea pockmarks had spectacularly higher biological productivity compared with surrounding sediment. The large complex 'Regab' pockmark on the Gabon continental margin seems to contain a novel and important fauna, chemosynthetic communities and carbonate concretions (Ondréas et al 2005, Gay et al 2006, Olu-Le Roy et al 2007). Three pockmarks farther north of the 'Regab' pockmark also seem to contain a high abundance of typical seep fauna (vesicomyid clams and vestimentiferan worms) (Sahling et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chemosynthetic communities, authigenic carbonates, and gas hydrates have been described for the giant Regab pockmark (see Fig. 1), which is 800 m in diameter and located close to the Congo Canyon (e.g., Charlou et al 2004;Ondréas et al 2005;Gay et al 2006c), and for the Kouilou pockmarks located north of the Congo Canyon (Sahling et al 2008;Haas et al 2010;Nöthen and Kasten 2011).…”
Section: Geological Settingmentioning
confidence: 99%
“…Seismic and geological data collected during several research cruises to the Congo Fan have been presented by Uenzelmann-Neben et al (1997), Uenzelmann-Neben (1998), Ondréas et al (2005), Gay et al (2007), and Sahling et al (2008). During ODP Leg 175, three holes were drilled north of the Congo Canyon (Wefer et al 1998).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation